1945
DOI: 10.1104/pp.20.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Activity and Duration of Life of Apples Gathered at Different Stages of Development and Subsequently Maintained at a Constant Temperature

Abstract: In Part I of this series (9) it was shown that the respiratory activity of an apple gathered at "maturity" in the autumn and subsequently kept at a constant temperature was characterized by a rise followed by a fall. This rise in respiratory activity was attributed to a change of state in the protoplasm. It was considered to mark the onset of senescence and was termed the "climacteric. " It is interesting to inquire whether the senescent rise occurs in fruit picked in an immature condition.Outline of the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

1947
1947
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 2 publications
2
30
0
Order By: Relevance
“…CO,, is highly effective in reversing the inhibition of elongation caused by 5 um IAA, and becomes progressively less effective at higher auxin levels because it cannot counteract the action of more than a ppm ethvlene (fig 1), the ethylene content of the tissue at 50 JuM IAA (4). Similarly, CO2 reinstates aulxin inhibited growth in pea roots (7), and it has been demonstrated that auxin inhibits growth in this tisstue by inducing ethylene formation (7) (24) proposed that 0., depletion might interfere with the production and action of ethylene. This suiggestion is stupported by the observation that fruiits evolve less ethylelne (6) 4 and(i 7 show I/Vn3 to be independent of (S) so that the behavior of the tis.sue at all inifinite concenitrationi of ethylene (1/A -0) caln be l)redicted by the low-er dashed line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO,, is highly effective in reversing the inhibition of elongation caused by 5 um IAA, and becomes progressively less effective at higher auxin levels because it cannot counteract the action of more than a ppm ethvlene (fig 1), the ethylene content of the tissue at 50 JuM IAA (4). Similarly, CO2 reinstates aulxin inhibited growth in pea roots (7), and it has been demonstrated that auxin inhibits growth in this tisstue by inducing ethylene formation (7) (24) proposed that 0., depletion might interfere with the production and action of ethylene. This suiggestion is stupported by the observation that fruiits evolve less ethylelne (6) 4 and(i 7 show I/Vn3 to be independent of (S) so that the behavior of the tis.sue at all inifinite concenitrationi of ethylene (1/A -0) caln be l)redicted by the low-er dashed line.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to form complexes with metals is a property of unsatutrated aliphatic compoutnds which is lacking in other aliphatic and all but a few aromatic molecules. The bonding in the complex is influienced by the availabilitv of electrons in the filled r-orbitals of the unsaturated compound, and also by the ease of overlap of these orbitals with those of the metal as determined by (24) proposed that CO., interferes wvith the action of ethylene. At the molecular level stuch an interactioni is not difficult to envision becauise CO, is a close structtural analogule of allene, a compound which substitutes for ethylene in hoth the pea growth aIndI fruiit ripening assays: O -C = O HC = C = CHI, HC --H., carbon dioxide alleine ethylene Since CO, possesses the essential strletuiral featuires needed for ethylene action, except that it lacks the terminal carbon atom ailel is negatively charged on 1)oth ends, might it not act as a competitive inhibitor of ethylene actioni?…”
Section: Discussionmentioning
confidence: 99%
“…The number of reports of ethylene production in the plant kingdom (5,11,13,14) and its association with other plant hormones (7,13) …”
Section: Discussionmentioning
confidence: 99%
“…CO2 interferes with responses of plant tissues to ethylene (8); leaf abscission is one response so affected (1). More recently, storage of fruits at reduced atmospheric pressure was shown to delay fruit ripening, apparently by hastening escape of endogenous ethylene (3)(4)(5).…”
mentioning
confidence: 99%